2020
DOI: 10.3389/fnut.2019.00189
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Patterns and Fluorosis in Guizhou, China

Abstract: Objective: Many studies have explored the effects of individual foods or nutrients on fluorosis, but no studies have focused on dietary patterns. This study examined the relationship between dietary patterns and coal-burning fluorosis in Guizhou, China. Methods: This 1:1 matched case-control study was conducted in Zhijin County of Guizhou province with a sample size of 200 cases of fluorosis and 200 age and gender matched controls. Habitual dietary intake was assessed by face-to-face interviews, using a valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In addition, the differences in dietary patterns among the local populace could also lead to differences in human intake. Some studies showed that the dietary pattern of consuming easy-to-roast foods had a significant linear trend with the risk of Fluorosis ( 59 ). Finally, some nutrients might reduce the effects of toxic elements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the differences in dietary patterns among the local populace could also lead to differences in human intake. Some studies showed that the dietary pattern of consuming easy-to-roast foods had a significant linear trend with the risk of Fluorosis ( 59 ). Finally, some nutrients might reduce the effects of toxic elements.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnoses of dental fluorosis (WS/T208-2011, China) and skeletal fluorosis (GB 16396–1996) were performed by a specialist from the CDC. A detailed description of the method is described in our previous studies ( 24 , 25 ). We used the following participant inclusion criteria: (1) participants must have lived in Zhijin County for at least 10 years; and (2) be between 18 and 75 years old.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnoses of dental fluorosis (WS/T208-2011, China) and skeletal fluorosis (GB 16396-1996) were performed by a specialist from the CDC. A detailed description of the method is described in our previous studies ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Urinary fluoride concentration was measured by the ion electrode method according to the standard WS/T 89-2015 (China). Further descriptions of the detection have previously been presented ( 20 , 21 ). Briefly, the urine sample was taken out from the refrigerator at −20°C and thawed at room temperature.…”
Section: Methodsmentioning
confidence: 99%